Training on how to make floating cage net for sea urchin culture at Desa Pisou, Central Sulawesi, Indonesia - Alfi Sahri Remi Baruadi; Sumrin Sumrin; La Nane (Fisheries and Society Publisher, 2021)
Sea urchin is an abundant fisheries resources in Pisou Village, Pagimana District, Central Sulawesi. This abundance is caused by the high productivity of sea urchins and the lack of utilization by the local community. The high density of sea urchins causes the poor quality of gonad and taste. This is mainly caused by the insufficient availability of food in the nature that can be only improved by aquaculture. This community empowerment was conducted in the Pisou Village for 5 weeks from February-March 2020. The aim of this program is to cultivate sea urchins in improving the quality of sea urchin gonad by aquaculture. Another goal is to educate the local fishers on how to culture and utilized the gonad a seafood and crackers. The result of this activity is the availability of floating net cages at Desa Pisou Village that can be used for sea urchin cultivation.